1985
DOI: 10.1038/317071a0
|View full text |Cite
|
Sign up to set email alerts
|

The ras oncogene product p21 is not a regulatory component of adenylate cyclase

Abstract: Harvey (Ha-MSV) and Kirsten (Ki-MSV) murine sarcoma viruses induce tumours in animals and transform various cells in culture because of the expression of the ras oncogene product, p21 (ref. 1). Proto-oncogenes homologous with these genes are highly conserved evolutionarily and activated ras oncogenes have been detected in many human cancers. Whether c-ras oncogenes are directly responsible for human carcinogenesis is uncertain; however, it is clear that p21 mediates virus-induced transformation, although by an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
84
0
1

Year Published

1986
1986
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(89 citation statements)
references
References 27 publications
4
84
0
1
Order By: Relevance
“…Yeast Ras proteins, members of small G proteins, structurally resemble mammalian ras oncogene products (Powers et al, 1984). Unlike mammalian Ras proteins, however, yeast Ras proteins activate adenylate cyclase (Beckner et al, 1985;Toda et al, 1985). By contrast, in mammalian cells, adenylate cyclase is activated by heterotrimeric G proteins (Gilmann, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Yeast Ras proteins, members of small G proteins, structurally resemble mammalian ras oncogene products (Powers et al, 1984). Unlike mammalian Ras proteins, however, yeast Ras proteins activate adenylate cyclase (Beckner et al, 1985;Toda et al, 1985). By contrast, in mammalian cells, adenylate cyclase is activated by heterotrimeric G proteins (Gilmann, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Although human H-ras could apparently complement a S. cerevisiae rasdefective mutation DeFeo-Jones et al, 1985), the human gene has been shown not to be involved in the control of adenylate cyclase (Beckner et al, 1985;Birchmeier et al, 1985), whereas regulation of this enzyme is the major role of the S. cerevisiae ras proteins (Toda et al, 1985). Hence further analysis of the function of S.pombe YPT family genes in S.pombe cells appears to be critical.…”
Section: Discussionmentioning
confidence: 99%
“…Thus it has been postulated that these proteins have an analogous function to that which G-proteins and transducin have in the amplification of extracellular signals. The human Ha-ras oncogene product, however, is not a component of adenylate cyclase (Beckner et al, 1985) and it does not seem to be specifically ADP-ribosylated. In addition, in a recent report by Birchmeier et al (1985) it was shown that human Ha-ras p21 proteins injected into oocytes induce maturation but do not change the cyclic AMP concentration.…”
Section: Inhibition Of [3h]gdp Binding Was Measured With Increasingmentioning
confidence: 99%